Islamic Theological Views on the Teachersâ Position and Duties - Lubis, Agus Salim (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
Some people always underestimateÂ teachers. AÂ person as teachers do not preserve their personality; whereas, from the side of tauhid, teaching profession is a very noble job and should be given a high honor. Why? Because the tasks undertaken by the teachers have the relationship with the existence of what has been done by God, Allah, to all His creators, as teaching, educating, leading, guiding, and preserving. On the other hand, a teacher must have a personality with divine attributes (rabbaniyah), such as love and gentle, honest, virtuous, patient, has a broad and deep knowledge, clean or avoid sin, humble and forgiving, and others.Â Keywords: Teacher, Theology, Islam.Copyright Â© 2015 by Al-Talim All right reserved